Automated multiwell fluorescence lifetime imaging for Förster resonance energy transfer assays and high content analysis. Issue 10 (21st May 2015) - Kelly, Douglas J.; Warren, Sean C.; Alibhai, Dominic; Kumar, Sunil; Alexandrov, Yuriy; Munro, Ian; Margineanu, Anca; McCormack, Jessica; Welsh, Natalie J.; Serwa, Remigiusz A.; Thinon, Emmanuelle; Kongsema, Mesayamas; et al.
<x xml:space="preserve">Abstract</x> An HCA-FLIM instrument is presented alongside exemplar oligomerisation, intermolecular and intramolecular FRET assays that require robust measurement of small lifetime changes.